Measurement of Function Post Hip Fracture: Testing a Comprehensive Measurement Model of Physical Function. Issue 4 (July 2016) - Resnick, Barbara; Gruber‐Baldini, Ann L.; Hicks, Gregory; Ostir, Glen; Klinedinst, Jennifer N.; Orwig, Denise; Magaziner, Jay
Abstract : Background: : Measurement of physical function post hip fracture has been conceptualized using multiple different measures. Purpose: : This study tested a comprehensive measurement model of physical function. Design: : This was a descriptive secondary data analysis including 168 men and 171 women post hip fracture. Methods: : Using structural equation modeling, a measurement model of physical function which included grip strength, activities of daily living, instrumental activities of daily living, and performance was tested for fit at 2 and 12 months post hip fracture, and among male and female participants. Validity of the measurement model of physical function was evaluated based on how well the model explained physical activity, exercise, and social activities post hip fracture. Findings: : The measurement model of physical function fit the data. The amount of variance the model or individual factors of the model explained varied depending on the activity. Conclusion: : Decisions about the ideal way in which to measure physical function should be based on outcomes considered and participants. Clinical Relevance: : The measurement model of physical function is a reliable and valid method to comprehensively measure physical function across the hip fracture recovery trajectory.